Bondaruk L. V. Myth criticism and myth criticism methodology of the literary work study: translation aspect (on the material of Marcel Proust’s novel «Noms de pays: le nom») - Bondaruk L. V. (Philological Treatises, 2020)
The article deals with the development and the formation processes of the methodology of myth criticism analysis of literary work on the basis of national and world systems. The author of the article analyzes the structural components and the ways of reproduction of myth and poetic elements in their projection on translation means. The problem of the reproduction of the author’s mythological world picture is considered on the material of Marcel Proust’s novel « Nom de pays: le nom ».